Effects of Low-Protein Diet Without Soybean Meal on Growth Performance, Nutrient Digestibility, Plasma Free Amino Acids, and Meat Quality of Finishing Pigs - Bobo Deng; Litong Wang; Xiaomei Jiang; Tianyong Zhang; Mingfei Zhu; Guoshui Wang; Yizhen Wang; Yuanzhi Cheng (Animals)
This study investigated the effects of a low-protein diet without soybean meal on the growth performance, nutrient digestibility, plasma-free amino acids, and meat quality of finishing pigs. A total of 81 barrows and 81 gilts ([Yorkshire × Landrace] × Duroc) of 150 days old with similar body weights (103.64 ± 3.65 kg) were selected and randomly allocated into three groups with three replicates in each group and 18 finishing pigs in each pen (4.5 m × 8.5 m). Three dietary formulations were established in this experiment: (1) 14% crude protein, and 14% soybean meal for the control group diet (CON); (2) 13% crude protein, and 7% soybean meal for half soybean meal group diet (HSB); (3) 12% crude protein, and 0% soybean meal for soybean meal free group diet (SBF). Three groups of diets were equal to standard ileal digestible amino acids and swine net energy. Results showed that (1) there was no significant difference in final body weight, average daily feed intake, and average daily gain in CON, HSB, and SBF groups (p > 0.05). However, the feed conversion rate was higher in the SBF but the differences were not significant (p = 0.08). (2) Compared with the CON group, the apparent digestibility of dry matter, crude protein, and calcium in the SBF group was significantly increased by 6.42%, 4.78%, and 9.82%, respectively (p < 0.05). However, ether extract and phosphorus did not differ significantly between the three groups (p > 0.05). All groups had no significant differences in serum biochemical indexes (p > 0.05). (3) Compared with the CON group, the plasma-free contents of glycine and glutamate in the HSB and SBF groups were significantly decreased by 42.90% and 37.06%, respectively (p < 0.05). Compared with the CON group, the contents of plasma-free histidine and valine in the SBF group were significantly decreased by 16.72% and 16.21%, respectively (p < 0.05), but there was no significant difference compared with the HSB group (p > 0.05). Compared with the CON group, plasma-free isoleucine content in the HSB group was significantly decreased by 50.39% (p < 0.05), but there was no significant difference compared with the SBF group (p > 0.05). (4) Backfat thickness in the SBF group was significantly increased by 3.53% compared with that in the CON group (p < 0.05), but there was no significant difference compared with the HSB group (p > 0.05). Compared with the CON group, lean meat percentage in the HSB and SBF groups showed a tendency to increase and decrease, respectively (p = 0.09). (5) The urine ammonia-nitrogen content of finishing pigs in the SBF group was significantly lower than that of the CON (p < 0.05), at a rate of 28.80%. H2S content in the urine of the SBF group tended to decrease (p = 0.06). This study demonstrates that a low-protein diet without soybean meal can be applied as a dietary strategy for finishing pigs with no adverse influence on growth performance.